Stable isotopes reveal that fungal residues contribute more to mineral-associated organic matter pools than plant residues. (May 2022) - Klink, Saskia; Keller, Adrienne B.; Wild, Andreas J.; Baumert, Vera L.; Gube, Matthias; Lehndorff, Eva; Meyer, Nele; Mueller, Carsten W.; Phillips, Richard P.; Pausch, Johanna
Abstract: We still lack crucial knowledge about the contribution of plant vs . microbial residues to specific SOM pools, particularly the relative contribution of arbuscular (AM), ectomycorrhizal (ECM), and saprotrophic (SAP) fungi. We investigated sources of particulate and mineral-associated organic matter (POM and MAOM) around trees with distinct mycorrhizal types, Liriodendron tulipifera (AM-association) and Quercus alba (ECM-association), in a temperate deciduous forest in Indiana, USA. Combining 13 C and 15 N natural abundance analyses with measurements of microbial residues using amino sugars, the isotope signatures of large, medium and small-sized POM and MAOM fractions were compared with those of leaves, roots and biomass of mycorrhizal and saprotrophic fungi. A Bayesian inference isotope mixing model calculated sources of C and N to SOM fractions. While the isotope composition of POM resembled that of plants, MAOM was close to fungal values. This was confirmed by mixing model calculations and microbial residue analysis, which additionally and independent from tree partner suggested saprobic fungi contributing with 4–53% to POM and 23–42% to MAOM, as opposed to ECM contributions. Our results suggest fungal, not plant residues, as the source of the most putatively stable OM pool; thus, altering fungal communities may enhance efforts to increase long-term soil C storage. Highlights: Plant vs. microbial input to SOM via Bayesian Inference Isotopic Mixing Model. Ectomycorrhizal and saprotrophic fungi are main contributors to MAOM. Amino sugar data confirmed a high contribution of fungal residues to MAOM. Consideration of the role of fungal functional groups in soil carbon storage.